Study of the mechanical compression properties of Rosa sterilis S.D. Shi based on FEM - Siqian Wang; Peixuan Mao; Wenxin Feng; Yufei Yang; Yuelong Yu; Xinyue Hou; Zhiping Xie (Scientific Reports)
Abstract Understanding the mechanical properties of Rosa sterilis S.D. Shi is important for the design and improvement of related mechanical equipment for planting, picking, processing, and transporting Rosa sterilis S.D. Shi. Compression damage is a common form of mechanical damage in agricultural products, especially during automated mechanical production. Therefore, this study establishes a three-dimensional model of seedless prickly pear fruit based on image processing technology and analyzes the compressive mechanical properties of seedless prickly pear under different directions through experiments combined with finite element method simulation. In both simulation and actual results, the average correlation coefficients were found to be 0.99 and 0.98 for the vertical compression direction and the horizontal compression direction, respectively. The above results show that our finite element compression model can provide a comprehensive understanding of the mechanical properties of Rosa sterilis S.D. Shi fruits under different directional loads. There is significant directional sensitivity in the compression resistance of Rosa sterilis S.D. Shi fruits have horizontal compression resistance greater than vertical compression resistance. The results of this study are of great significance for the development of mechanized automation in the Rosa sterilis S.D. Shi industry and for ensuring the quality of Rosa sterilis S.D. Shi fruits.